Allah-Conscious Character Education for Teachers at SMP PK Muhammadiyah Al-Kautsar Kartasura - Setiyo Purwanto; Siti Zulaekah; Dyah Intan Puspitasari; Mutalazimah Mutalazimah; Yuli Kusumawati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The moral decline of adolescents that currently occurs caused has not maximized the formation of character. The COVID-19 pandemic is a challenge for schools in building student character. This devotion aims to inform the teachers regarding Allah-conscious character education in realizing students who are Sidiq, Amanah, tabligh, and fathonah. This devotion is located at SMP PK Muhammadiyah Al-Kautsar with two meetings. The participants of this service were four counseling guidance teachers and a teacher from the school student affairs department. The material is delivered through lectures and interactive discussions. The material provided is “Allah-Conscious Character Education” and “Counseling Techniques in Adolescents”. This activity went well and smoothly. The teachers participated in this activity with fantasies and being active in the discussion session. Hopefully, this teacher mentoring activity can improve the teacher's ability to build a student’s character and improve teacher counseling techniques. Suggestions for teachers to continuously improve teacher performance in shaping character and for parents and the schools to work together to maximize student character formation.